PENGEMBANGAN KUSUKA (BUKU SAKU FISIKA) BERBASIS KONSTRUKTIVISME SEBAGAI MEDIA PEMBELAJARAN FISIKA DI SEKOLAH MENENGAH ATAS (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The aim of this research is to develop KUSUKA (Buku Saku Fisika) based on constructivism as a valid physics learning media in senior high school. This type of research is Research and Development (R&D) using the ADDIE ID model. The development of KUSUKA has been done by considering the pocketbook theory as a learning media and constructivism theory. The data was collected through the validation sheet by the validators. The validated aspects consist of content feasibility, language feasibility, presentation feasibility, and graphic feasibility which is adapted from textbook assessment by BSNP 2014. Validation results are obtained average of Aiken’s validity indeks for all aspects is 0,88. It can be concluded that KUSUKA was valid based on constructivism.Keywords: Physics Learning Media, Physics Pocketbook, Constructivism